PENGEMBANGAN VIDEO PENDIDIKAN SEKSUAL SEBAGAI UPAYA EDUKASI DALAM MENCEGAH PELECEHAN SEKSUAL DI SEKOLAH DASAR - Nadelia Maudi; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Universitas Tanjungpura, 2022)
AbstractThis study aims to develop a sexual education video as an educational effort to prevent sexual harassment of students at Abdi Agape Elementary School, North Pontianak. The research method used is the research and development (RnD) method by adapting the Borg and Gall model with potential and problem steps, data collection, product design, design validation, design revision, product testing, and product revision. The data are quantitative data and qualitative data. Quantitative data were obtained from the results of the product assessment by the validator and the results of filling out the questionnaire responses to videos by teachers and students. Qualitative data were obtained from suggestions/comments by validators, teachers and students. Research instruments in the form of interviews and questionnaires. The level of validity of the video is based on the results of the assessment by media experts and material experts, while the response to the video is based on the results of responses by teachers and students. The results of the validation of sexual education videos obtained an average of 3,825. Based on the results of the research and discussion, it was concluded that sexual education videos had a level of validity in the